Erratum to: Synthesis and in vitro evaluation of melatonin entrapped PLA nanoparticles: An oxidative stress and T-cell response using golden hamster : SYNTHESIS AND IN VITRO EVALUATION OF MELATONIN ENTRAPPED PLA NANOPARTICLES (Journal of Biomedical Materials Research Part A, (2015), 103, 9, (3034-3044), 10.1002/jbm.a.35441) - Pandey S.K.; Haldar C.; Vishwas D.K.; Maiti P. (My University, 2025)
The authors regretfully submit that there was human mistake and it can be rectified by adding a corrigendum/erratum in which the following be mentioned: Fig 2A and 2D incorrect one be immediately replaced by the Fig 2A and 2D corrected one. The human mistake was due to folders having electron micrograph of all experiment and during transfer of images from technical person to us. The authors would like to apologies for inconvenience caused. (Figure presented.). © 2018 Wiley Periodicals, Inc.